O IMPÉRIO DA LEI SOBRE A VIDA: A tensão dialética entre lei e graça no pensamento crítico de Franz Hinkelammert - FREITAS, KERLINGTON PIMENTEL DE (2020)
Tensions are inherent to life in society and diverse and adverse interests permeate it throughout its existence. The law, whether civil, economic or religious is inserted, engenders and organizes all life in society, so this law becomes a dimension of all human socialization and, when executed, it becomes an instrument of injustices becoming on the contrary. On the other hand, we see the poor as a component of this instrumentalized socialization, becoming an object of exploitation, whether economic, sexual or religious that Franz Hinkelammert systematizes in his criticism and work in the focus and study of the law, identifying it as an instrument of “sins” when complied with and applied to the target subject of this law, stating that this law, when executed, from the point of view of justice for compliance with the law, is executed fairly, causing injustices. We will deal with the utopia of grace, in the current economic system, pointing out the concept of the limit of feasibility erected by Hinkelammert, that is, the possibility of the object in practice. Not everything is possible. Then, by the criterion of feasibility, the circumstances and effects of the action are analyzed, the conditions of objective possibility are considered (material and formal, empirical, technical, economic, political and others) so that the act is effectively possible. In this way, we analyze the dialectical tension between law and grace in the critical thinking of Franz Hinkelammert, through bibliographic researches carried out in his vast work, as well as in renowned authors who research the subject in the most diverse thematic areas, emphasizing mainly on (a) the role of laws in social systems and the social division of labor; (b) the tension between the concepts of law and grace and lastly, (c) the utopia of grace and its application across the limit of factibility.